Komunitas Pedesaan di Malaysia : Masalah Dan Tantangan - Teuku Afrizal (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Community development is an effort to improve the standard of living and quality of life of the community. The Wawasan Village Movement Program is a program that focuses on the development of rural human development towards a village that is more advanced, attractive and profitable. Even though in its implementation, community development is running smoothly and successfully. However, post-success needs to be maintained and sustainable. This article focuses on problems and challenges in the context of rural community development through the Wawasan Village Movement program. This article takes a case study in the Village of Shadow Keningau, Sabah Malaysia. Data collection was carried out through in-depth interviews, focus group discussions and observations. As well as documentation of published and unpublished materials. The article found several important facilitators who became problems and challenges after the successful implementation of the Village Movement Movement program in Keningau Shadow Village. This includes; (i) no further action from the government after the success; (ii) difficulty maintaining existing committees; (iii) idle and using assets for a long time; (iv loosening of social ties. In short, after the success of the government, it is necessary to give encouragement and encouragement to the Desa Bayangan community by making this village a model village. In addition, taking community members as facilitators in fostering other Wawasan Village Movement villages that are being fostered.